Motivations and Family Functioning of Foster Families in Italy. Issue 44 (8th August 2018) - Migliorini, Laura; Rania, Nadia; Cardinali, Paola; Guiducci, Valentina; Cavanna, Donatella
ABSTRACT: The aim of this paper was to investigate foster family care to better understand this unique care-giving context. The research objective was to understand motivation, family functioning, and individual attachment styles in foster families. Participants were 33 foster parents who completed a questionnaire that included the motivations for choosing foster care, the relationship with the birth family and with social service workers, a measure of family functioning and adult attachment. The motivations for becoming a foster family were very different between families with a birth child and families without a birth child. The results showed that for the foster mother, the relationship with the birth family constituted a very critical element of the fostering experience. The same trend emerged in the relationship with the minor. The results showed that foster families were cohesive and expressive. With respect to attachment style, foster parents had lower scores than a normative sample on the discomfort with closeness, the tendency to consider relationships as secondary and the need for approval subscales. These results have implications for the practices of social work for foster family support and developing a shared commitment to the needs of the foster family in terms of both resources and weaknesses.